The association between obesity and severe disability among adults aged 50 or over in nine high-income, middle-income and low-income countries: a cross-sectional study. Issue 4 (2nd April 2015) - Koyanagi, Ai; Moneta, Maria Victoria; Garin, Noe; Olaya, Beatriz; Ayuso-Mateos, Jose Luis; Chatterji, Somnath; Leonardi, Matilde; Sainio, Päivi; Galas, Aleksander; Haro, Josep Maria
Abstract : Objective: The association between obesity and disability may differ between high-income and low-income/middle-income countries but there are no studies comparing this association between these settings. The aim of the study was to assess this association in nine countries using nationally-representative data from the Collaborative Research on Ageing in Europe (COURAGE) study and the WHO's Study on global AGEing and Adult Health (SAGE). Design: Population-based cross-sectional study Setting: The survey was conducted in China, Finland, Ghana, India, Mexico, Poland, Russia, South Africa and Spain between 2007 and 2012. Participants: 42 116 individuals 50 years and older. The institutionalised and those with limited cognition were excluded. Primary outcome measure: Disability was defined as severe or extreme difficulty in conducting at least one of six types of basic activities of daily living (ADL). Results: The mean body mass index (BMI) ranged from 20.4 kg/m 2 in India to 30.7 kg/m 2 in South Africa. Compared to normal BMI (18.5–24.9 kg/m 2 ), BMI≥35 kg/m 2 was associated with significantly higher odds for ADL disability in Finland (OR 4.64), Poland (OR 2.77), South Africa (OR 2.19) and Spain (OR 2.42). Interaction analysis showed that obese individuals in high-income countries were more likely to have ADL limitations than those in low-income or middle-income countries. Conclusions: The higher odds for disability among obese individuals in high-income countries may imply longer life lived with disability due to factors such as the decline in cardiovascular disease mortality. In South Africa, this may have been due to the exceptionally high prevalence of class III obesity. These findings underscore the importance of obesity prevention to reduce the disability burden among older adults.